Diversity assessment tool for agrobiodiversity and resilience (DATAR) - Integrate intra-specific diversity of crop, livestock and aquatic resources in to agericultural development decision making. - Jarvis, Devra I.; Fonteneau, A.; Nankya, R.; Turdieva, M.K.; Gauchan, D.; Tempelmann, K.; López Noriega, Isabel (2019)
The Diversity Assessment Tool for Agrobiodiversity and Resilience (DATAR) allows local and national development organizations to integrate intra-specific crop, livestock and aquatic diversity into their decision making plans to improve on farm productivity for small holder farmers. DATAR 9 is an IT tool with a Back Office Web App for national administrators, scientists and project leaders, an Android App for Researcher in the field, and an Android App for Farmers. The application has three main modules: agrobiodiversity data, agrobiodiversity interventions and agrobiodiversity impact.